ANALISIS EKSPOR NON-MIGAS DI INDONESIA - Adnan, Muhammad (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Indonesia's economic growth in 2022 is 5.31%, more significant than pre-Covid 19. One of the reasons is an export performance that grows quite well. In 2022, Indonesia's trade balance amounted to USD 54.46 billion, the highest surplus in history. Indonesia's non-oil and gas exports are one of the national development priorities to encourage the optimization of state revenues. Indonesia's non-oil and gas exports in 2022 reached USD275.96 billion, an increase of 25.80% compared to the previous year. This study aims to analyze the effect of economic growth, exchange rates, and inflation on the value of non-oil and gas exports in Indonesia. This study is an associative quantitative study. The data used in this research is secondary data in the form of time series data from 1970-2021. The data were analyzed using the Vector Error Correction Model (VECM). Based on the results of the study, long-term growth has a positive and significant effect on the value of Indonesia's non-oil and gas exports. In contrast, exchange rates and inflation negatively and significantly affect the value of Indonesia's non-oil and gas exports. The results show that economic growth, exchange rates, and inflation do not significantly affect the value of Indonesia's non-oil and gas exports in the short term. The government needs to maintain the stability of macroeconomic indicators in order to increase the value of non-oil and gas exports and maintain non-oil and gas export commodities. The government must also be aware of the risk of non-oil and gas export demand from trading partner countries so far and develop non-oil and gas exports to countries other than their trading partners.